How Users Search the Mobile Web: A Model for Understanding the Impact of Motivation and Context on Search Behaviors - Wu Dan; Zhu Man; Ran Aihua (Journal of Data and Information Science, 2017)
This study explores how search motivation and context influence mobile Web search behaviors.